Burnout and depressive symptoms are not primarily linked to perceived organizational problems. Issue 9 (21st October 2018) - Bianchi, Renzo; Mayor, Eric; Schonfeld, Irvin Sam; Laurent, Eric
ABSTRACT: In this 257-participant study (76% female; mean age: 44.84), we examined two ideas that are widespread among burnout researchers: (a) the idea that burnout is primarily related to occupational-level factors; and (b) the idea that burnout should be considered a sentinel indicator in research on negative occupational outcomes. We investigated the links between burnout and a series of generic and work-related variables, namely, depressive symptoms, neuroticism, extraversion, effort-reward imbalance in the job [ERI], social support at work (SSW), and turnover intention. Burnout was assessed with the Shirom-Melamed Burnout Measure, depressive symptoms with the PHQ-9, neuroticism and extraversion with the NEO-Five Factor Inventory, ERI with the 10-item version of the Effort-Reward Imbalance Questionnaire, SSW with the Job Content Questionnaire, and turnover intention with a dedicated 3-item measure. Correlation, multiple regression, and relative weight analyses were conducted. Burnout was not found to be more strongly linked to organizational and work-contextualized variables than to personality traits. In addition, turnover intention was not associated to a greater extent with burnout than with ERI. Burnout and depressive symptoms were highly correlated and exhibited overlapping nomological networks. Overall, our findings question the way burnout has been generally conceived.